THE IMPORTANCE OF HEALTH, HYGIENE, AND PREVENTIVE MEASURES IN ISLAM - Rabiul Alam (International Journal of Islamic and Complementary Medicine, 2026)
The whole of Islam is a complete way of life, most clearly demonstrated by its foundational emphasis on health and hygiene. This study presents a comprehensive comparison between Islamic thought on cleanliness and the scientific views of modern biological, medical, and environmental teachings. The central idea of this study is the combination of physical purity (Taharah) with spiritual purity, a contrasting idea that elevates basic hygiene to a compulsory act of worship. The study explains a sophisticated framework for public health that predates modern germ theory by exploring specific revelations from the Holy Quran, including a detailed interpretation of Surah Al-Fatir, and the Prophetic Sunnah (Hadith). The study explores the benefits of ablution (Wudu), the value of traditional tooth cleaning (Miswak), and the wisdom of early quarantine protocols. In addition, the study explores the toxicological and nutritional rationale behind dietary laws in Islam, especially the concepts of Halal and Tayyib. The study also suggests that Islamic teaching on health is not merely a set of ritual procedures but a holistic and sustainable system that remains strikingly aligned with contemporary global health guidelines established by organizations such as the World Health Organization.   ABSTRAK Islam secara keseluruhan merupakan suatu cara hidup yang lengkap, yang paling jelas ditunjukkan melalui penekanannya yang mendasar pada kesehatan dan kebersihan. Penelitian ini menyajikan perbandingan komprehensif antara pemikiran Islam tentang kebersihan dengan pandangan ilmiah dalam ajaran biologi, kedokteran, dan lingkungan modern. Gagasan utama penelitian ini adalah integrasi antara kemurnian fisik (taharah) dan kemurnian spiritual, suatu konsep yang mengangkat praktik kebersihan dasar menjadi bagian dari ibadah yang wajib. Penelitian ini menjelaskan kerangka kesehatan masyarakat yang canggih, yang telah ada sebelum berkembangnya teori kuman modern, melalui eksplorasi ayat-ayat Al-Qur’an, termasuk interpretasi mendalam terhadap Surah Al-Fatir, serta Sunnah Nabi (Hadis). Studi ini juga mengkaji manfaat wudu, nilai penggunaan siwak sebagai alat pembersih gigi tradisional, serta hikmah di balik penerapan konsep karantina sejak dini. Selain itu, penelitian ini membahas rasionalitas toksikologis dan nutrisi dalam hukum makanan Islam, khususnya konsep halal dan tayyib. Penelitian ini menunjukkan bahwa ajaran Islam tentang kesehatan bukan sekadar serangkaian praktik ritual, melainkan suatu sistem yang holistik dan berkelanjutan, yang tetap selaras dengan pedoman kesehatan global modern seperti yang ditetapkan oleh World Health Organization